Paving the Way for Reliable Alzheimer's Disease Blood Diagnosis by Quadruple Electrochemical Immunosensing. Issue 9 (16th March 2022) - Valverde, Alejandro; Gordón Pidal, José M.; Montero‐Calle, Ana; Arévalo, Beatriz; Serafín, Verónica; Calero, Miguel; Moreno‐Guzmán, María; López, Miguel Ángel; Escarpa, Alberto; Yáñez‐Sedeño, Paloma; Barderas, Rodrigo; Campuzano, Susana; et al.
Abstract: Alzheimer's disease (AD), the most common neurodegenerative disorder, demands new cost‐effective and easy‐to‐use strategies for its reliable detection, mainly in the preclinical stages. Here, we report the first immunoplatform for the electrochemical multidetermination of four candidate protein biomarkers in blood, neurofilament light chain (NfL), Tau, phosphorylated Tau (p‐Tau) and TAR DNA‐Binding Protein 43 (TDP‐43). It involves implementation of sandwich‐type immunoassays and enzymatic labelling with horseradish peroxidase (HRP) on the surface of magnetic microbeads (MBs). Amperometric detection is performed after depositing the magnetic immunoconjugates on disposable quadruple transduction platforms by monitoring the enzymatic reduction of H2 O2 mediated by hydroquinone (HQ). The immunoplatform achieved LOD values smaller than the content of target biomarkers in plasma of healthy subjects, with RSD values<5 %, and lower cost and shorter assay time (60–90 min) than other available methodologies and was applied to the analysis of plasma from healthy controls and AD patients. Abstract : A quadruple immunoplatform for the amperometric determination of AD‐candidate protein blood biomarkers (neurofilament light chain, NfL, Tau, phosphorylated Tau, p‐Tau and TAR DNA‐Binding Protein 43, TDP‐43) to assist in the reliable and minimally invasive Alzheimer's disease diagnosis was developed.